2021
DOI: 10.3390/md19110594
|View full text |Cite
|
Sign up to set email alerts
|

Halophilic Carotenoids and Breast Cancer: From Salt Marshes to Biomedicine

Abstract: Breast cancer is the leading cause of death among women worldwide. Over the years, oxidative stress has been linked to the onset and progression of cancer. In addition to the classical histological classification, breast carcinomas are classified into phenotypes according to hormone receptors (estrogen receptor—RE—/progesterone receptor—PR) and growth factor receptor (human epidermal growth factor receptor—HER2) expression. Luminal tumors (ER/PR-positive/HER2-negative) are present in older patients with a bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 178 publications
(206 reference statements)
0
7
0
Order By: Relevance
“…genera it is common to find bisanhydrobacterioruberin as the more abundant C50 carotenoid [ 13 , 40 ]. In the case of astaxanthin found in Halorubrum tebenquichense SU10, other xanthophylls were reported in Halobacterium and Haloferax species, principally canthaxanthin or haloxanthin [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…genera it is common to find bisanhydrobacterioruberin as the more abundant C50 carotenoid [ 13 , 40 ]. In the case of astaxanthin found in Halorubrum tebenquichense SU10, other xanthophylls were reported in Halobacterium and Haloferax species, principally canthaxanthin or haloxanthin [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haloarchaeal carotenoids, in particular bacterioruberin, are especially exciting as they might represent the first case of extremolytes with a demonstrated therapeutic effect in vitro. Bacterioruberin, a rare C 50 carotenoid synthesized by most haloarchaea has been shown to exhibit the highest antioxidant capacity of all known carotenoids, including ß-carotene (Mandelli et al 2012 ), and were recently shown in in vitro studies to have a cytotoxic effect on human breast cancer lines (Giani et al 2021 , 2023 ). A novel C 50 carotenoid were also recently identified from Natrialba sp.…”
Section: Extremophiles and The Sustainable Development Goalsmentioning
confidence: 99%
“…There is preclinical evidence of the preventive effects of lycopene on mouse cutaneous tumors in the promotion phase, via stimulation of NRF2 signaling pathway, and p62-mediated degradation of Keap1, via the autophagy-lysosomal pathway [ 38 ]. Recent studies have shown that the halophilic carotenoid bacterioruberin from haloarchae may have a promising future due to its particular structure and antioxidant activity [ 39 ].…”
Section: Natural Antioxidants In the Prevention And Treatment Of Brea...mentioning
confidence: 99%